Ramadan observance is associated with higher fatigue and lower vigor in athletes: a systematic review and meta-analysis with meta-regression - Trabelsi, K.; Ammar, A.; Boujelbane, M. A.; Khacharem, A.; Elghoul, Y.; Boukhris, O.; Aziz, A. R.; Taheri, M.; Irandoust, K.; Khanfir, S.; Chtourou, H.; Clark, C. C. T.; et al. (International Review of Sport and Exercise Psychology, 2025)
Systematic reviews and meta-analyses examining the effects of Ramadan observance on athletes` mood states are lacking. Thus, this systematic review and meta-analysis aimed to identify the impact of Ramadan observance on athletes` mood states assessed using validated scales. Six electronic databases (PubMed, Web of Science, Scopus, Wiley, Taylor & Francis, Scielo) were used to search for relevant studies conducted among athletes during Ramadan. Studies that included assessments of mood states, using validated scales, in athletes were included. The quality of the selected studies was scored using the QualSyst assessment checklist. Eighteen studies were selected, of which 15 were of strong quality and the remaining three studies were rated as moderate quality. Ramadan observance resulted in significantly higher fatigue scores (g = 0.781, 95% CI 0.481-1.08, p < .001) and lower vigor scores (g = -0.297, 95% CI -0.493 to -0.101, p = .003), with no significant change in depression, confusion, anger, and tension scores (p > .05). Continuation of training during Ramadan increased feelings of fatigue and lowered vigor. Collaboration between mental and physical fitness coaches is needed to maintain the balance between workload and recovery during Ramadan observance. Future primary studies with greater methodological rigor are warranted.